If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5(x + 1) + -2(x + -1) = 12 Reorder the terms: 5(1 + x) + -2(x + -1) = 12 (1 * 5 + x * 5) + -2(x + -1) = 12 (5 + 5x) + -2(x + -1) = 12 Reorder the terms: 5 + 5x + -2(-1 + x) = 12 5 + 5x + (-1 * -2 + x * -2) = 12 5 + 5x + (2 + -2x) = 12 Reorder the terms: 5 + 2 + 5x + -2x = 12 Combine like terms: 5 + 2 = 7 7 + 5x + -2x = 12 Combine like terms: 5x + -2x = 3x 7 + 3x = 12 Solving 7 + 3x = 12 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-7' to each side of the equation. 7 + -7 + 3x = 12 + -7 Combine like terms: 7 + -7 = 0 0 + 3x = 12 + -7 3x = 12 + -7 Combine like terms: 12 + -7 = 5 3x = 5 Divide each side by '3'. x = 1.666666667 Simplifying x = 1.666666667
| -(v+9)+7=-7v-12 | | -15x+8=7-15x | | 9p+7=6+3(p-1) | | x=x^2+6x+15 | | 9q+7=6+3(p-1) | | 3x+7=-2x-23 | | Ln(3)+ln(2)=ln(x) | | -7(s+10)+11=-5s-6 | | 6y+10=4+6y+6 | | .55x=2 | | 24-8x=1-11x | | 4-2(3x-5)+x=7(1-3x) | | 1/3h+4=8 | | y=(x-4)/5 | | 3-2(x-1)+4x=5-(2-x) | | -2/3(6x-12y) | | 9(t-9)-11=-6t+10 | | 5w+2=-1+3(w-10) | | X/3-21=14 | | 4-2(3x-5)+x=7-(1-3x) | | X/6-17=14 | | 3x-2(x+4)=2x-3 | | 5x+-5=20 | | 8W+2W-7=23 | | 7+4x-4t=-11 | | 19x-13=25 | | 8x-2+3x=5x+10 | | (2+(2-(2+(2-(2+r)))))=1 | | -7y-2=-6y-6 | | 3(2+5x)+3=2(1-3x) | | 2x+3(1x-10)=45 | | (x^2+1)= |